The Venous Antithrombotic Profile of Naroparcil in the Rabbit - Millet, Jean; Theveniaux, Jocelyne; Brown, Neil L (Thrombosis and Haemostasis, 1994)
The venous antithrombotic profile of naroparcil or (4-[4-cyanoben-zoyl]-phenyl)-1.5-dithio-β-D-xylopyranoside was investigated in the rabbit following single i. v. and oral administration. Naroparcil attenuated thrombus development in a Wessler stasis model of venous thrombosis (jugular vein) employing bovine factor Xa as a thrombogenic stimulus giving ED50 values of 21.9 mg/kg and 36.0 mg/kg after respectively i. v. and oral administration. Venous antithrombotic activity was maximal 2-3 h after i. v. administration and 4-8 h after oral administration. Four hours after the oral administration of maximal antithrombotic (Wessler model, factor Xa) doses (100 and 400 mg/kg), naroparcil had no significant effect on bleeding time. In platelet poor plasma obtained from animals treated 4 h previously with various doses (25 to 400 mg/kg) of naroparcil, there was no detectable anti-factor Xa nor antithrombin activity. Similarly, naroparcil had no effect on APTT nor on thrombin time. A sensitized thrombin time (to about 35 s) was modestly but significantly increased following oral administration of the compound at 400 mg/kg. However, thrombin generation by the intrinsic pathway was reduced in a dose-related manner, maximal reduction being 65% at 400 mg/kg. The same doses of naroparcil enhanced the formation of thrombin/heparin cofactor II complexes at the expense of thrombin/antithrombin III complexes in plasma incubated with (125I)-human a-thrombin and induced the appearance of dermatan sulfate-like material in the plasma of treated rabbits, as measured by a heparin cofactor II-mediated thrombin inhibition assay. The results suggest that naroparcil could have a safe venous antithrombotic profile following oral administration (antithrombotic effect compared to bleeding risk). It is probable that part of the mechanism of action of the β-D-xyloside, naroparcil, is due to the induction of chondroitin sulfate-like glycosaminoglycan biosynthesis, this material being detectable in the plasma.